Plasminogen activator inhibitor-1 is associated with leukocyte telomere length in American Indians: findings from the Strong Heart Family Study - Peng, Hao (J Thromb Haemost, 2017)
BACKGROUND: Plasminogen activator inhibitor-1 (PAI-1) promotes cellular aging both in vitro and in vivo. Telomere length is a marker of biological aging. OBJECTIVES: To examine the cross-sectional and longitudinal associations between plasma PAI-1 and leukocyte telomere length in a large-scale epidemiological study of American Indians. METHODS: We measured leukocyte telomere length (LTL) and plasma PAI-1 in 2,560 American Indians who were free of overt CVD and participated in the Strong Heart Family Study (SHFS) clinical exam in 2001–2003. LTL and PAI-1 were repeatedly measured in 475 participants who attended SHFS clinical visits in both 2001–2003 and 1998–1999. Generalized estimating equation model was used to examine the cross-sectional and longitudinal associations between PAI-1 and LTL, adjusting for known risk factors. RESULTS: A higher level of plasma PAI-1 was negatively associated with shorter age-adjusted LTL (β=−0.023, 95%CI: −0.034 ~ −0.013). This association was attenuated (β=−0.015, 95%CI: −0.029 ~ −0.002) after adjustments for demographics, study site, lifestyle (smoking, drinking, physical activity), and metabolic factors (obesity, blood pressure, fasting glucose, insulin, lipids, kidney function). Further adjustment for hsCRP did not change this association (β=−0.015, 95%CI: −0.029 ~ −0.001). Longitudinal analysis revealed that change in plasma PAI-1 was also inversely associated with change in LTL after adjusting for demographics, follow-up years, lifestyle factors, changes in metabolic factors, baseline levels of PAI-1 and LTL (β=−0.0005, 95%CI: −0.0009 ~ −0.0001). CONCLUSIONS: A higher level of plasma PAI-1 was associated with shorter LTL in American Indians. This finding may suggest a potential role of PAI-1 in biological aging among American Indians.